Production rate and cost comparison of ceramic block solar desalination unit (CBSDU) with basin type solar still (BSS) - Islam, Md Hamidul; Bari, Quazi Hamidul; Islam, Md Shafiqul (International Journal of Advanced Geosciences, 2016)
Distilled water for drinking purposes is vital especially in semi or arid countries where surface water is limited and groundwater is saline. The ceramic block solar desalination unit (CBSDU) is significant for single household in developing countries like Bangladesh. The aims of this study are to monitor daily production and cost compared with basin type solar still (BSS). The materials and installation cost of the ceramic block solar unit was estimated Tk.40 per solar desalination unit. The field experiment was carried out on the roof top of the civil engineering building, KUET from 24th February to 11th June, 2012. The CBSDU was installed perpendicular to the surface, from 2 feet above the surface, on a concrete base. The collection bottle was put under the concrete base. The distilled water was collected every day at least two hours after sunset. The average production was found 4.26 lit/m2/day. The CBSDU offers 12% less cost than BSS. Single household can easily use CBSDU for their drinking water in coastal belt of Bangladesh.
Keywords: Ceramic Block; Coastal Belt; Drinking Water; Production; Solar Desalination.